Study on strength and durability characteristics of polypropylene fiber reinforced blended concrete tiles - K. Amudhavalli, N; Harihanandh, M (International Journal of Engineering and Technology, 2018)
Concrete is brittle and widely used as an artificial construction material with incorporation of cement, water and aggregate in necessary proportions. To overcome the brittle behavior of composites, fibers and admixture are added to the concrete. In this present investigation Polypropylene Fiber is added in varying percentage (0.2%, 0.4%, 0, 6%, 0.8% and 1%) to the weight of cement and constant percentage of Rice Husk Ash (15%) is replaced with cement. The polypropylene fiber reinforced blended concrete tiles of size 300mm x 300mm x 30mm are cast as per the code and tested at 28 days curing period. Flexural strength, Abrasion test, Dimensional quality and water absorption are studied. Among different proportion of Polypropylene Fiber Reinforced Blended Concrete, the best performance is achieved by the combination of 15% of Rice Husk Ash with 0.6% of Polypropylene Fiber.Â Â